1983
DOI: 10.1002/bms.1200100303
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of N4-trideuteroacetylsulphamerazine and its metabolites sulphamerazine and N4-acetylsulphamerazine in man by means of high-performance liquid chromatography and mass spectrometry

Abstract: The synthesis, high-performance liquid chromatographic and mass spectrometric analysis of N4-trideuteroacetylsulphamerazine is described. N4-trideuteroacetylsulphamerazine in man is deacetylated into sulphamerazine, which in turn is acetylated again into N4-acetylsulphamerazine. The existence of a deacetylationacetylation equilibrium in man has been demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1983
1983
1997
1997

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Similar results have been found with N-acetylprocainamide (NAPA) where only 2.8% of the administered NAPA-13C was metabolized by deacetylation (Stec et al, 1980). In contrast, the existence of a deacetylation-acetylation equilibrium in man has been demonstrated with a sulphonamide, N4-acetyl-sulphamerazine (Vree et al, 1983). The success in demonstrating such an equilibrium depends on the position of the equilibrium.…”
Section: Short Report 613supporting
confidence: 66%
See 1 more Smart Citation
“…Similar results have been found with N-acetylprocainamide (NAPA) where only 2.8% of the administered NAPA-13C was metabolized by deacetylation (Stec et al, 1980). In contrast, the existence of a deacetylation-acetylation equilibrium in man has been demonstrated with a sulphonamide, N4-acetyl-sulphamerazine (Vree et al, 1983). The success in demonstrating such an equilibrium depends on the position of the equilibrium.…”
Section: Short Report 613supporting
confidence: 66%
“…Since acetylation is the major pathway for the elimination of 5-AS we investigated if an equilibrium exists between its acetylation and deacetylation to see whether reversible N-acetylation might contribute to the action of 5-AS. Such reversibility of acetylation has been observed with some sulphonamides (Schroder, 1973;Vree et al, 1981Vree et al, , 1983 and might also occur with other acetylated drugs.…”
Section: Introduction Methodsmentioning
confidence: 58%
“…Vree et al reported deacetylation of acetylsulphamerazine (13,15), acetylsulphapyridine (16) and acetylsulphamethoxazole (16) in humans. Nouws et al reported the same for acetylsulphadimidine in calves (5) and carp (6), and acetylsulphatroxazole in calves (8).…”
Section: Discussionmentioning
confidence: 99%
“…Althpugh many metabolic pathways have been identified for sulphonamides, and especially in ruminants hydroxylation is the main metabolic pathway (2,3,19), it is well recognized that the main elimination route is the acetylation followed by renal excretion through the active transport system in many species other than dogs (14). Shimoda et al de-Acetylated metabolites of sulphonamides are deacetylated to their parent compounds in many species, including pigs (7,11,12), calves (5), and humans (13,15,16). Since these animal species have an extensive acetylation capacity, deacetylation of acetylated metabolites of sulphonamides has been recognized to be a part of the acetylation-deacetylation equilibrium and therefore to be an important factor affecting sulphonamide pharmacokinetics.…”
Section: Introductionmentioning
confidence: 99%